Smoking fish in Shortland Islands - Atu, Stenneth; Kiyo, Wilson; Eriksson, Hampus (Ministry of Fisheries and Marine Resources, 2024)
The Ministry of Fisheries and Marine Resources (MFMR) fisheries policy aims to facilitate sustainable use of inshore and inland fisheries for rural men and women that access, use and benefit from them, through improved preservation, market access and enhanced livelihood opportunities. Accordingly, the MFMR has carried out research to identify challenges and opportunities in the smoked fish value chain. This brief summarises some of the findings, including the origins and development of Shortland Islands smoked fish production from a traditional subsistence form to a marketable commodity. The focus is on the process from fish landing through to sales, and the gender differentiation of roles in production and marketing.